Effect of Nitrogen on Yield Attributes, Yield and Nitrogen Use Efficiencies of Buckwheat in Mustang, Nepal - Bastola, Arjun; Bharatee, Prakash; Chhantyal, Sunil (Agronomy Journal of Nepal, 2025)
Nitrogen (N) play important role in the vegetative, reproductive characteristics and grain yield of buckwheat. To evaluate the effect of nitrogen on growth, yield attributes, yield and nitrogen use efficiencies on buckwheat a field experiment was operated during July to October of 2024 in Mustang district of Nepal consisting of five nitrogen level viz. control (0), 20, 40, and 80 kg N ha-1 in randomized complete block design which was replicated four times. Data on plant height, number of lateral branches per plant, yield attributes and yield were measured and analysis was done using R-stat software. Data on analysis shows that shows that plant height was found tallest in 80 kg N ha-1 in all the days of observations while there was no effect of N on number of lateral branches per plant. Yield attributes like number of fruit cluster per plant (19.16), number of grains per plant (89.04) and per cluster (4.78) and grain yield (662.5 kg ha-1) were found significantly highest in 60 kg N ha-1 while stover yield (2771.76 kg ha-1) was measured significantly more in in 80 kg N ha-1 while harvest index was recorded highest in in 60 kg N ha-1. Nitrogen use efficiencies like partial factor productivity was recorded more in 20 kg N ha-1 while agronomic efficiency was highest in 60 kg N ha-1. Thus, 60 kg N ha-1 was found good in growth, yield attributes, yield and agronomic efficiency based on this research findings.